Local Democracy in the West-Nordic Countries - Grétar Þór Eyþórsson (Nordicum-Mediterraneum, 2020)
In 2012, the research project West Nordic municipal structure. Challenges to local democracy, efficient service provision and adaptive capacity was granted money from the Arctic Co-operation Programme 2012-2014. The overall aim of the project was to collect knowledge on the local level in the three West Nordic countries; the Faroe Islands, Greenland and Iceland by mapping the situation and development in the municipal sectors, focusing primarily on four aspects. The first was; the municipal structure. The second was; the democratic aspect – that is, which consequences the structural development has had for local democracy – to identify the main challenges to democracy, caused by the structural developments. The third; to map the service production capacity and effectiveness of the municipalities, and the fourth; to try to map the municipalities’ capacity to manage the development processes which often accompany municipal amalgamations. An overall research question was: What consequences have developments in municipal structure in the three countries had for democracy, local self-government and autonomy, as well as the ability to manage the processes accompanying amalgamations? In September 2014 a report containing this analysis was submitted . In this article I use the data from this survey to answer following main research questions: What is the general status of local democracy in the three countries? Is there a connection between size and democracy when we are looking at municipalities in a small scale size as is the case in the West Nordic countries? Does peripheral or central position in a municipality affect the attitudes towards democracy as measured in the survey reported? The operationalization of local democracy is threefold: First, looking at the perception of power and influence by different territories in each municipality. Second, looking at the perceptions of access to the municipal administration. The third is by looking at the perception of ties and contacts to the local politicians.